Undernutrition and dietary diversity score and associated factors among lactating mothers in Northwest Ethiopia - Belay, Mahider Awoke (Frontiers in Nutrition, 2024)
Background: Maternal undernutrition has a negative influence on maternal and child health, and economic and social development. Limited research has been conducted on both the nutritional status and dietary diversity score among lactating mothers. Therefore, the present study aimed to determine the magnitudes of undernutrition and dietary diversity scores and their associated factors among lactating mothers in Bahir Dar City, northwest Ethiopia.A community-based cross-sectional study was conducted from March to May 2021.Systematic random sampling and interview-administered questionnaires were employed. Dietary diversity score and nutritional status were measured using 24 hour recall and body mass index, respectively. Data entry and analysis were performed using EpiData version 3.02 and SPSS version 24 software, respectively. Both the bivariable and multivariable binary logistic regression analyses were performed, and the strength of association was measured in terms of odds ratio.The prevalence of undernutrition and low dietary diversity scores among respondents were 13.5% (95% CI; 10.4, 17.2) and 64.8% (95% CI, 60.0, 69.4), respectively. The significant factors for undernutrition were being young [AOR= 2.30, 95% CI (1.09, 5.43)], having low dietary diversity score [AOR=2.26, 95% CI (1.01,5.10)], having poor nutritional knowledge [AOR=2.56, 95% CI (1.03, 6.51)], meal frequency less or equal to 3 times per day [AOR=4.06, 95% CI (.71, 9.65)], primary school [AOR=3.20, 95% CI (1.01, 9.11)], and husband's secondary school [AOR=2.28, 95% CI (1.25, 8.53)]. Age between 20 and 30 years [AOR=1.46, 95% CI (1.01, 2.48)], being food insecure [AOR=3.41, 95% CI (1.21, 9.63)], and being poorest [AOR=2.31, 95% CI (1.02, 5.32)] were associated with the dietary diversity score.A high prevalence of undernutrition and low dietary diversity scores were recorded in the current study area. Age, educational status of lactating mothers and their husbands, nutritional knowledge, dietary diversity, and meal frequency were significant factors associated with undernutrition. Age, food security, and wealth index were associated with the dietary diversity score.